Trends of banned pesticides and PCBs in different tissues of striped dolphins (Stenella coeruleoalba) stranded in the Northwestern Mediterranean reflect changing contamination patterns. (January 2022) - Dron, Julien; Wafo, Emmanuel; Boissery, Pierre; Dhermain, Frank; Bouchoucha, Marc; Chamaret, Philippe; Lafitte, Daniel
Abstract: Although banned for years, organochlorine pesticides and PCBs continue to affect aquatic life, dolphins being particularly exposed. The concentrations of 31 PCB congeners, and 15 banned pesticides or metabolites were measured in 5 tissues of 68 striped dolphins stranded in the Northwestern Mediterranean coast in 2010–16. The results were compared to historical data (1988–2009) and, even though there is a slow decreasing trend, the levels in the 2010–2016 samples were still elevated based on common cetacean toxicological thresholds. A transition period in 2007–08, probably caused by a morbillivirus epizootic amplified the stranding, espacially of highly contaminated specimens. From 2010, higher proportions in parent compounds towards metabolites were observed yet again. These changing patterns were likely reflect the exposure of dolphins to the remobilization of pollutants from contaminated soils and sediments, with a prominent role of rivers. This should lead to an even slower decline of these contaminants that could last for decades, requiring new efforts to reduce their dispersal to aquatic ecosystems. Graphical abstract: Unlabelled Image Highlights: Banned organochlorine contaminants globally decreased in dolphins since 1988. Global levels remain elevated and still constitute a threat to dolphins. Levels of parent compounds towards metabolites reflect a shift in contaminants origin. Increasing parent compounds suggest diffusion from contaminated lands and sediment. Morbillivirus epizootic likely affected preferably highly multi-contaminated dolphins.